2010
DOI: 10.1007/s11912-010-0092-5
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Quality of Life Research Among Head and Neck Cancer Patients

Abstract: Head and neck cancer often has a marked impact on multiple spheres of functioning. A rapidly expanding literature has examined the functional and psychosocial sequelae that patients experience over the trajectory of the disease. This review considers some of the salient developments in quality-of-life (QOL) research over the past decade. Selected findings are summarized regarding assessment of QOL in head and neck cancer, acute and long-term sequelae, clinical and psychosocial determinants, and intervention pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 52 publications
1
29
2
Order By: Relevance
“…Since many of depressive symptoms are somatic, once a patient is identified as having higher depressive symptoms, clinicians need to evaluate the patient in light of individual symptoms, characteristics, and circumstances. It is also important to evaluate how much disruption the symptoms are causing in the patient's life [16,30,34]. Additional research with a larger sample size is needed to identify patient characteristics and symptoms in the oropharyngeal and laryngeal cancer population that predict severe depression at later time points.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since many of depressive symptoms are somatic, once a patient is identified as having higher depressive symptoms, clinicians need to evaluate the patient in light of individual symptoms, characteristics, and circumstances. It is also important to evaluate how much disruption the symptoms are causing in the patient's life [16,30,34]. Additional research with a larger sample size is needed to identify patient characteristics and symptoms in the oropharyngeal and laryngeal cancer population that predict severe depression at later time points.…”
Section: Discussionmentioning
confidence: 99%
“…The radiation experience for the patient is a time of uncertainty and complexity since individuals come for 6 to 9 weeks of treatments 5 days a week, manage treatment side effects at home as outpatients, and require many other appointments with treatment team members (e.g., nutritionist, physician, nurse, and pharmacist) regarding their symptoms. Patients are unsure about relief of symptoms, management of daily living, treatment outcomes, and possibility of recurrence [1,3,16,38]. Since patient uncertainty levels remained high even at 1 month after completion of treatment, there is a question as to what will happen to these high levels of uncertainty when patient's are at home recovering from treatment, dealing with symptom self-management, and waiting for 3-month follow-up scans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others felt that they had demands from themselves and/or from their employer to return to full-time work too soon (23). Some had concerns about unemployment after sick leave such as being laid off from work and having to find a new job (10). Interestingly, some patients found that the disease had made them realise that work is not everything and that other things in life should be prioritised.…”
Section: The Return To Work (47 Patients)mentioning
confidence: 99%
“…Patients often suffer from different sequelae from the cancer itself, side effects of treatment, and individual factors such as unhealthy eating habits and alcohol and tobacco abuse [7]. Frequent sequelae are trismus, swallowing problems, dry mouth, shoulder disability, lymphedema, speech impediments, altered physical appearance, and psychological distress [8][9][10]. The process of returning to work is problematic in some HNC survivors but not all.…”
Section: Introductionmentioning
confidence: 99%